Potensi antibakteri ekstrak daun gendola (Basella alba Linn var. rubra) terhadap Escherichia coli dan Staphylococcus aureus - Diah Muldianah; Marsah Rahmawati Utami; Jekmal Malau (Journal of Pharmaceutical and Sciences, 2023)
Gendola leaves (Basella alba Linn var. rubra) have long been utilized as an alternative treatment for various bacterial infections. This study aims to evaluate and determine the most potent antibacterial activity among three different extracts of gendola leaves, namely n-hexane extract, ethyl acetate extract, and 70% ethanol extract against Staphylococcus aureus and Escherichia coli. The research followed a laboratory-based experimental approach that involved maceration extraction using three different solvents and antibacterial activity testing through the well-diffusion method. Each extract was assessed at five different concentrations (20%, 40%, 60%, 80%, and 100% w/v) and compared to positive control chloramphenicol (0.3% v/v) and negative control DMSO (10% v/v). The results showed that only the n-hexane extract exhibited no antibacterial activity. In contrast, the ethyl acetate and 70% ethanol extracts exhibited more effective antibacterial activity against Staphylococcus aureus than Escherichia coli, with ethyl acetate extract displaying the most potential antibacterial activity.